Cooperative Banks: Backbone for the Development of Rural Economy - Agarwal, Shubham (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
Transforming agriculture and the rural economy has been accorded high priority by Government of India. In this context, government envisaged the transformative idea of “Doubling Farmers Income by 2022”. Capital formation in rural economy is of critical importance for increasing agricultural productivity and off-farm employment. Being a part of Indian financial system, the Cooperative banking system play an important role especially at the rural level as these banks characterized by a relatively comprehensive network extending to the grass root level and have intimate knowledge of the character and financial position of members and the local production possibility and chances of growth. These banks promote thrift and saving among their member and mobilise their small saving for productive or other useful purpose. Cooperative banks have a clear advantage over commercial banks for financial inclusion and the operating cost of these banks are also consider minimum from other financial institutions. This paper focuses on the Cooperative banks which are a feasible option for inclusive financial growth through rural development by creating opportunity for employment income and generation. Keywords: Cooperative Banks; Credit Flow; Banking Services; Agriculture Credit.